Death and memory in the rock: Newly discovered medieval rock-cut complex of Ohanavan - Khechoyan, Mher; Mirijanyan, Dianna; Simonyan, Hasmik (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
Among a number of early medieval martyriums (Aghtsk, St. Hripsime, St. Gayane, St. Mesrop Mashtots, Talin, Karenis, Amaras, Tigranakert, etc., all in Armenia), the crypt of Ohanavan stands out for its architectural composition and spatial solutions. The present article is devoted to the preliminary study of the newly revealed complex, the discovery of which complements the series of similar structures known to date and provides new data about the memorial structures of the early Christian period.